SYSTEMATIC LITERATURE REVIEW: PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID BERMUATAN ETNOMATEMATIKA - Tania, Dhea; Sulistyaningsih, Dwi; Purnomo, Eko Andy (TRANSFORMASI, 2025)
This study maps the direction and trends of research related to the development of Android-based learning media containing ethnomathematics in mathematics learning. The method used is a Systematic Literature Review (SLR) with the PRISMA protocol. Fourteen articles that had been selected according to the specified characteristics were analyzed. The results indicate four development models used: ADDIE, Borg and Gall, Procedural, and 4D. There was an increase in research activity in 2021, and geometry (specifically flat-sided solids) became the main focus of research. Furthermore, the study demonstrated that the integration of technology, culture, and material characteristics has an influence on strengthening the meaningfulness of learning. This research needs to followed up by adapting materials and technology to the needs and available devices.